Analysis of potential drug interaction in children under 10 years of age with acute respiratory tract infections at RSIA Sitti Khadijah hospital in Makassar - Nurhikma Awaluddin; Tenry Wahyuni; Dwi Yulianti Alifah; Astika Ekawati Putri; Ghina Ramadhani (Faculty of Pharmacy, Universitas Pancasila, 2026)
Acute Respiratory Tract Infection (ARI) is one of the most prevalent diseases, triggered by various factors such as microorganisms and air pollution. This study aimed to analyze the risk of drug interactions in pediatric ARI patients under 10 years of age at RSIA Sitti Khadijah Makassar from July to December 2024. A non-experimental retrospective design was applied using data collected from outpatient medical records.The findings indicated that 75% of patients having potential drug interactions predominantly in the moderate category with a pharmacodynamic mechanism. The primary factor contributing to these interactions was the concurrent use of multiple drugs. Such interactions can alter therapeutic effectiveness by either enhancing or reducing drug effects; therefore, early identification and appropriate management of drug interactions are essential to optimize treatment outcomes and minimize adverse effects. Greater attention to potential drug interactions in pediatric ARI therapy is crucial to ensure treatment safety and effectiveness.